Strategi dan Tantangan Manajemen Rantai Pasok Produk Telur Ayam Ras : Suatu Tinjauan Literatur Sistematis: Strategies and Challenges in the Supply Chain Management of Breed-Specific Chicken Eggs: A Systematic Literature Review - Debora Natalia; Dyan Linasari; Lala Wulandari; Zian Fachrian (OGZ Research & Publishing, 2026)
Objective: Supply chain management plays a crucial role in ensuring the availability and smooth distribution of commercial chicken eggs, which are a widely consumed food commodity. Various studies on the commercial chicken egg supply chain have been conducted, but they generally address aspects of supply chain management, distribution, or marketing separately. This study aims to identify, analyze, and synthesize research findings on supply chain management strategies and challenges for commercial chicken eggs using a Systematic Literature Review (SLR) approach. Methods: This study employed a systematic literature review method in accordance with the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were obtained through a literature search in several scientific databases using keywords related to supply chain management, distribution, marketing, and commercial chicken eggs. Based on a selection process using inclusion and exclusion criteria, 14 articles were identified and analyzed as primary studies. Research Results: The success of the commercial chicken egg supply chain is influenced by coordination among business actors, the integration of product, information, and financial flows, and effective distribution management. Commonly implemented distribution strategies include coordination among actors and the management of an efficient distribution system, while marketing strategies focus on selecting marketing channels that can improve efficiency and the farmers’ share. The main challenges identified include fluctuations in feed prices, changes in market demand, supply disruptions, distribution delays, and fluctuations in commercial egg prices. This study concludes that the success of the commercial egg supply chain management requires good coordination among stakeholders, efficient distribution management, and marketing strategies capable of maintaining supply and price stability to support business sustainability.